Urgensi Visum ET Repertum Pada Tahap Penyidikan Dalam Mengungkap Tindak Pidana Penganiayaan - Wahid, St. Hadijah; Maharani, Alisa; Muhammad Azhar Nur (ILIN Institute, 2023)
The research objective to determine the urgency and obstacles to post mortem et repertum in uncovering criminal acts of persecution at the Sinjai Police Station. This type of research is included in the type of phenomenological research with a qualitative approach method. The subjects of this study were Investigators from the Criminal Investigation Unit of the Sinjai Police. The data collection methods are interviews and documentation. While the data analysis uses data collection techniques, data reduction, data presentation and drawing conclusions. The results of the study show that the urgency of visum et repertum at the investigative stage in uncovering criminal acts is as valid evidence, as a basis for detaining suspects, as a consideration for judges in making decisions, and as a substitute for evidence. While the obstacles to visum et repertum in disclosing criminal acts are caused by internal factors, namely the high number of general criminal cases handled by investigators and the lack of investigative personnel causing the handling of cases to experience obstacles. As for external factors, namely reports that often come late from the victim, doctors who handle post mortem are still lacking and often do not exist, medical equipment at Sinjai Hospital is not complete, the victim's family refuses to be examined and requests for post mortem et repertum psychiatry takes a long time to publish.